Preoperative refraction, age and optical zone as predictors of optical and visual quality after advanced surface ablation in patients with high myopia: a cross-sectional study - Zhou, Jiaqi; Knorz, Michael C. (BMJ open, 2018)
Objective To investigate the factors associated with optical and visual quality of advanced surface ablation in high myopia. - Design A cross-sectional study of high myopic eyes treated with laser epithelial keratomileusis (LASEK)/epipolis laser in situ keratomileusis (Epi-LASIK). - Setting6 Eye and ENT Hospital of Fudan University in Shanghai. - Methods One hundred and thirty-eight high myopic eyes (138 patients) (myopia −6 D or more) were examined more than 12 months after LASEK or Epi-LASIK with advanced surface ablation on the MEL 80 excimer laser (Zeiss AG, Jena, Germany). Refraction, higher order aberrations (HOAs) and contrast sensitivity before and after surgery were evaluated. Factors including preoperative refraction, age, gender, central corneal thickness, pupil size, optical diameter, ablation depth and flap creation method were analysed for association with postoperative high-order aberration, contrast and glare sensitivities, and different analytic diameters. - Results HOAs increased significantly postoperatively (p<0.05), with the most significant change found in Z(spherical aberration). At a 5 mm analysis diameter, increased coma was associated with age; increased spherical aberration difference was associated with age, optical zone diameter and method of epithelial flap creation. At a 3 mm analysis diameter, none of the factors contributed to changes in HOAs. Higher preoperative refractive error was associated with decreased contrast and glare sensitivity at each spatial frequency. - Conclusion A larger optical zone diameter design is recommended to achieve better visual quality in advanced surface ablation for high myopia correction. Age and preoperative refraction may help predict postoperative visual quality.
Gesehen am 19.10.2020